Hybridity and Friction in Organizational Politics: New Perspectives on the African Security Regime Complex. Issue 2 (14th March 2020) - Moe, Louise Wiuff; Geis, Anna
ABSTRACT: Security governance in Africa constitutes a web of interactions between national, regional, and international organizations. This emerging 'African security regime complex' receives growing attention in International Relations debates on international organizations (IOs). Most analysis, however, follows institutionalist and problem-solving approaches, centred on regulatory concerns. We offer a different perspective. Moving beyond dominant perspectives on organizations as either pre-given institutional 'wholes' or rationalized 'tools' of states, we instead unpack the 'politics of organizations', understood as the multiple processes and forms of agency through which organizations emerge, diversify and transform. In doing so, we bring IO analysis into conversation with debates on hybridity, friction and translocality.